Feeding habit study of Pelagic Fish which Caught in the Area of seagrass with different densities in Pulau Panjang, Jepara - Niniek Widyorini (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2010)
Seagrass bed on the shallow water area is a very important ecologically. It plays very important roles to the life of many kinds of fish, such as: as the nursery ground, feeding ground, spawning ground or just passing by. Of course, type and species of the fish itself will influence it. The growth of some individual and population highly related with the food existence in the area where they live. This research aimed to discover the food habit of pelagic fish, which caught in the seagrass area with different densities. The research was carried out for 2 months (July – August 2004). The research method that used was descriptive method, which had case study character. The sampling method to catch the fish was done using purposive sampling method . The determination of the research location was carried out with the mapping, which divided the seagrass area into 3 sampling stations based on its densities, which were high, medium and low density. The fish was caught using Gill net with 0.5 inch in mesh size. Based on the food habit analysis of food proportion that was obtained in the fish gut, the phytoplankton from the cyanophyta class was largely found. It caused by the high abundance of phytoplankton form this class in the waters. Meanwhile, the zooplankton group that dominated the waters was from entomostraca class. Most of the catched fish in three stations with different densities were omnivore. Ke y Word : Feeding Habit, Area of Seagrass, Pulau Panjang Jepara